Profile of clients tested HIV positive in a voluntary counseling and testing center of a district hospital, Udupi, South Kannada - Kumar A; Kumar P; Gupta M; Kamath A; Maheshwari A; Singh S (Wolters Kluwer Medknow Publications, 2008)
Background: The growing menace created by the HIV/AIDS (human immunodeficiency virus/acquired immunodeficiency syndrome) has alarmed not only the public health officials but also the general community. The Voluntary Counseling and Testing Centre (VCTC) services have begun as a cost-effective intervention in reversing this epidemic. Objectives: 1. To study the sociodemographic characteristics of HIV-positive clients and their risk behaviors. 2. To elucidate the reasons for their visit to the VCTC and know the problems anticipated by the clients after revealing their HIV-positive status. Study Design: A cross-sectional record-based study. Materials and Methods: The study was conducted in August 2007 among clients who tested positive for HIV in the VCTC of a district hospital in Karnataka from January to July 2007. Results: Study included 249 individuals, of whom 64.7% were males, 88.7% (age, 15-49 years), married (72.7% males and 84.0% females) and literate (females 71.5% and males 85.7%). A high percentage of nonresponse regarding the pattern of risk behavior was noted among the subjects (males: 42.8% and females: 90.9%). Of the individuals who responded, 91 males (98.9%) and 6 females (75.0%) had multiple heterosexual sex partners, while 1 male had homosexual partner. The figures in females show that two (25%) of them had a history of blood transfusion. The reason for visiting the VCTC were cited as some form of illness (33.3%), confirmation of test results (32.9%), family members diagnosed as HIV positive (12.9%) and 11.6% were referred from Directly Observed Treatment Scheme (DOTS) center. More than three quarter of the sample population anticipated discrimination at the time of medical treatment. Conclusion: People have begun using VCTC services, which reflects a change in their attitude toward HIV. The study provides us a clue to formulate an effective approach to educate people as well as the health personnel who are thought of as one of the important sources of discrimination.